APINEMA Asociación Peruana de Investigación en Educación Matemática - Bonilla, María del Carmen; Ricaldi Echevarria, Myrian Luz; Torres Céspedes, Isabel Zoraida; Huamán Avendaño, Nancy Juvisa (UNIÓN - REVISTA IBEROAMERICANA DE EDUCACIÓN MATEMÁTICA, 2014)
APINEMA Asociación Peruana de Investigación en Educación Matemática